EFFORT TO IMPROVE STUDENTS MATHEMATICS TEAMWORK LEARNING SKILL USING TYPE OF COOPERATIVE LEARNING COURSE REVIEW HORAY (CRH) - Herli Munira; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2018)
Students were demanded to get a good mark on each subject; nevertheless, their teamwork learning skills were lack asked to participate in the learning process. This research had the aim to improve the students' mathematics teamwork learning skills using the model of cooperative learning CRH. This research was a type of classroom action research. Subjects of research were the student's VII D grades of SMP Negeri 11 Yogyakarta on even semester in the academic year of 2016/2017. The object of research was mathematics teamwork learning skills using the model of cooperative learning CRH. The data collecting technique consisted of an interview, observation, triangulation, and test. The instrument of the research consisted of observation sheets and interview guides. This research was conducted in two cycles. The cycle was stopped after the result of the indicator was reached out to a minimum of 61% or good criteria. The research results showed that the model of cooperative learning CRH could improve VII D grades students' mathematics teamwork learning skills. It was proved that there was an increase in every cycle from the result of observation analysis toward students. In cycle 1, the percentage of students' teamwork learning skills reached out 50 % in enough criteria. Then, cycle II increased to be 69,93 % in good criteria. It means that there was an increase of 19,93 %. Based on the result of the interview with the students, it also showed that there was a positive response from the students.